MARAWIS PENGUATAN IDENTITAS ISLAM MASYARAKAT BETAWI - Heryanah, Heryanah (P2KK LIPI, 2004)
Most people in Indonesia have already known about Betawi’s folk art, such as, Lenong Betawi, Topeng Betawi, Gambang Kromong and so forth. Beside that, there is also another art, called Marawis. It exists in Betawi’s community since about 1970, and recently it begins to protrude and flourish. Marawis is an art of music percussion, which is played by a group of men, and usually use for some various Betawi’s ceremonies, like wedding, pengajian (majlis), and some other ceremonial events. The main instruments are Marawis and Hajir. The songs mostly in Arabic language comprising Islamic values. Hence, there are still some intense debate about the originality of this music, some people said that this kind of folk art is from Middle East countries, but the other believed that this is belong to Indonesian people. Nowadays, it seems that Marawis is considered to become one of Betawi’s culture.